2013
DOI: 10.1002/j.1532-2149.2013.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tibolone on osteoarthritis in ovariectomized rats: Association with nociceptive pain behaviour

Abstract: Treatment with tibolone attenuated the development of OA, concomitantly reduced nociception and increased serum alkaline phosphatase in ACLT + OVX rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…The results of OA score and the histopathological and immunohistochemical data of TGF-β were only compared amongst groups for the right (injury) legs. In our previous study 42 , the OA scores and histopathological findings of the contralateral non-injury legs showed normal findings.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The results of OA score and the histopathological and immunohistochemical data of TGF-β were only compared amongst groups for the right (injury) legs. In our previous study 42 , the OA scores and histopathological findings of the contralateral non-injury legs showed normal findings.…”
Section: Discussionmentioning
confidence: 71%
“…OVX interferes with estrogen production and increases bone and cartilage turnover. OVX alone has been shown to produce signs of OA in rats 4 and to increase OA pathology in traumatic OA models in the rabbit 41 and rats 42 . The prevalence of OA is higher in post-menopausal women than in men 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Ovariectomy (OVX) in rats has been proposed as a model of postmenopausal OA although the changes in knee cartilage observed after OVX are relatively mild and cartilage turnover may be transient [41]. Nevertheless, the combination of ACLT and OVX in rats represents a model of OA and bone loss that may be useful to test chondroprotective interventions [42,43]. We have recently reported the suitability of this model for the evaluation of drugs targeting cartilage and bone alterations [44].…”
Section: Introductionmentioning
confidence: 99%
“…Han et al (2007) reported that oyster shell increases the femur BMD and BV/TV in the OVX mice, indicating a potential for the cure of osteoporosis. Tibolone attenuated the development of osteoarthritis, concomitantly increasing serum ALP in the OVX-induced osteoporosis model (Yang et al 2014). This study revealed that PPE or Arg are able to successfully reduce the estrogen deficiency-induced bone loss.…”
Section: Discussionmentioning
confidence: 57%